Anatomic Double-Bundle Posterior Cruciate Ligament Reconstruction - Chahla, Jorge (Arthrosc Tech, 2016)
The posterior cruciate ligament (PCL) is known to be the main posterior stabilizer of the knee. Anatomic single-bundle PCL reconstruction, focusing on reconstruction of the larger anterolateral bundle, is the most commonly performed procedure. Because of the residual posterior and rotational tibial instability after the single-bundle procedure and the inability to restore the normal knee kinematics, an anatomic double-bundle PCL reconstruction has been proposed in an effort to re-create the native PCL footprint more closely and to restore normal knee kinematics. We detail our technique for an anatomic double-bundle PCL reconstruction using Achilles and anterior tibialis tendon allografts.